Cardiotonic properties of high density lipoproteins - L. E. Panin; A. R. Kolpakov; R. A. Knyazev; N. I. Tsirelnikov (Атеросклероз, 2013)
The ability of rat plasma high density lipoproteins (HDLs) to increase the frequency and amplitude of isolated rat heart contraction without considerable increase of oxygen consumption was revealed in Langendorf model. 30 min perfusion of solution with adrenalin in the regime of recirculation diminished the contractility of myocardium and increased heart oxygen consumption. The addition of HDLs in the perfusion solution protected the heart from the negative adrenalin action. The established inotropic effects of HDLs may have various mechanisms and make high density lipoproteins pоssible candidates for the endogenous digitalis-like compounds.